Types and causes of deviant workplace behavior in public organization in Malaysia. - Sathappan, Malini (Asian Scholars Network, 2021)
Deviant workplace behaviour is a paradox issue at universal level. Deviant workplace behaviour need to be studied by scholars to reduce harmful effects to employees such as job dissatisfaction, low performance, turnover intention and stress among employees. On the other hand it also involves high social and economic cost towards the organization. The aim of the study is to explore types and its causes of Deviant workplace behaviour at law enforcement agency. Data was collected among police officers in Selangor state involving various departments. The study found “at risk behaviour” was a cause of 2 types of misconduct such as alcohol consumption and drugs.